A comprehensive review of the factors predicting technical difficulty in laparoscopic cholecystectomy - Menon, Aravind (International Surgery Journal, 2017)
Laparoscopic cholecystectomy is the most common laparoscopic procedure performed all over the world. It has now become the gold standard management for symptomatic gallstones. Aim of the study was to identify and highlight the predictive factors determining intra operative technical difficulty in laparoscopic cholecystectomy. A database search was done in Medline, Google scholar and Journal seek using keywords ‘Laparoscopic Cholecystectomy’, ‘difficult cholecystectomy’ and ‘predictive factors’. 54 abstracts were shortlisted out of which 15 were selected based on the time of publication (after 2005), size of study group, relevance to the title, level of evidence and the journal of publication. Results were compared and reviewed and the conclusion was reached. Fifteen papers were reviewed based on literature search and statistically significant variables predicting the technical difficulty in Laparoscopic cholecystectomy was found. These were age, sex, obesity, previous upper abdominal surgeries, comorbid diseases like Diabetes, acute cholecystitis, raised WBC counts, gall bladder wall thickness more than 3mm, presence of pericholecystitic collection, single impacted stone, multiple stones, contracted gall bladder, adhesions at Calot’s triangle, intrahepatic gall bladder, complications like gangrenous GB and fistulisation. The predictive risk factors reviewed here need to be kept in mind by the laparoscopic surgeon during a laparoscopic cholecystectomy. Though none of them is an absolute contraindication, presence of these factors demand modifications in technique for a safe laparoscopic surgery.